The relationship of part-time work experience in college to academic performance and success in post-college employment - Laminta, Alma C. 1944- (s.n.], 1969)
The study analyzed the relationship of participation in part-time work while in college to the following variables: academic performance, and success in securing post-college employment. Findings show that work on a part-time basis is an advantage for the college student.